Dual Tasks in Older Adults: Inte Dual-task training in older adults: a key strategy for preserving physical and cognitive function (Revista Chilena de Rehabilitación y Actividad Física, 2025)
not applicable
Keywords: physical and cognitive function; Dual-task training; elderly people